A new pipeline for astrometry and photometry of asteroids. Issue Volume 14:Issue A30(2018) (August 2018) - Klç, Y.; Kaplan, M.; Eker, Z.
Abstract: Using Python 3, astropy and astrometry.net, we have developed a pipeline to obtain photometric light curves of asteroids automatically queried by the SkyBoT database from sequential FITS images. The pipeline provides: pre-reduction of data, astrometry, standard differential photometry and light curves by auto-selecting multiple comparison stars (maximum user-defined) from NOMAD catalog via VizieR. The code is an open source, free and hosted on GitHub with the GNU GPL v3 license.